Association between oral microbiome diversity and kidney stones: a cross-sectional study - Zhang, Zufa; Guan, Sheng; Chen, Li; Jiang, Fengze; Dong, Huqiang; Chen, Zuyi; Lv, Long; Song, Hongxuan; Sun, Weibing; He, Danni; Jiang, Sixiong; Tian, Feng (Frontiers in Microbiology, 2025)
BackgroundKidney stones are a common urologic disorder that imposes a significant burden on global public health. This study aimed to determine the association between oral microbiome diversity and kidney stones.MethodsThe data for this study came from the National Health and Nutrition Examination Survey 2009–2012 survey cycle. Use of alpha diversity to assess oral microbiome diversity. Multivariate logistic regression modeling was used to assess the association between different alpha-diversity indicators and kidney stones. Subgroup analyses and interaction tests were used to assess the stability of the association between alpha-diversity and kidney stones. Restricted cubic spline plots were used to assess non-linear associations and dose-response relationships.ResultsThe study included 5,870 eligible participants with a mean age of 43.74 years at baseline. After adjusting for all covariates, the observed oral microbiome diversity was significantly negatively associated with the risk of kidney stones (P < 0.05). Subgroup analyses showed that oral microbiome diversity was negatively associated with the risk of kidney stones in certain populations, particularly among those aged 40–60 years, men, obese, with moderate to high cardiovascular health scores, smokers, and those without hypertension. Restricted cubic spline analysis suggested a significant non-linear negative correlation between the Shannon and Simpson diversity indices and the risk of kidney stones (p for non-linear < 0.05). Since our study was a cross-sectional design, the main limitation was the inability to prove causality.ConclusionsIn this study, we found an inverse relationship between oral microbiome diversity and kidney stone risk observed in alpha diversity. This reveals the complexity of host-microbiome interactions, and further mechanistic studies are necessary to elucidate these complex roles in the future.